Blood transcriptome responses in patients correlate with severity of COVID-19 disease - Wang, Ya; Schughart, Klaus; Pelaia, Tiana Maria; Chew, Tracy; Kim, Karan; Karvunidis, Thomas; Knippenberg, Ben; Teoh, Sally; Phu, Amy L.; Short, Kirsty R.; Iredell, Jonathan; Thevarajan, Irani; et al. (Frontiers in Immunology, 2023)
Coronavirus disease 2019 (COVID-19) is an infectious disease caused by severe acute respir-atory syndrome coronavirus 2 (SARS-CoV-2). Infected individuals display a wide spectrum of disease severity, as defined by the World Health Organization (WHO). One of the main factors underlying this heterogeneity is the host immune response, with severe COVID-19 often associated with a hyperinflammatory state. Our current study aimed to pinpoint the specific genes and pathways underlying differences in the disease spectrum and outcomes observed, through in-depth analyses of whole blood transcriptomics in a large cohort of COVID-19 patients. All WHO severity levels were well represented and mild and severe disease displaying distinct gene expression profiles. WHO severity levels 1-4 were grouped as mild disease, and signatures from these patients were different from those with WHO se-verity levels 6-9 classified as severe disease. Severity level 5 (moderate cases) presented a unique transitional gene signature between severity levels 2-4 (mild/moderate) and 6-9 (se-vere) and hence might represent the turning point for better or worse disease outcome. Gene expression changes are very distinct when comparing mild/moderate or severe cases to healthy controls. In particular, we demonstrated the hallmark down-regulation of adaptive immune response pathways and activation of neutrophil pathways in severe compared to mild/moderate cases, as well as activation of blood coagulation pathways. Our data revealed discrete gene signatures associated with mild, moderate, and severe COVID-19 identifying valuable candidates for future biomarker discovery.